From Infrared Spectra to Macroscopic Mechanical Properties of sH Gas Hydrates through Atomistic Calculations - Shaden M. Daghash; Phillip Servio; Alejandro D. Rey (Molecules, 2020)
The vibrational characteristics of gas hydrates are key identifying molecular features of their structure and chemical composition. Density functional theory (DFT)-based IR spectra are one of the efficient tools that can be used to distinguish the vibrational signatures of gas hydrates. In this work, ab initio DFT-based IR technique is applied to analyze the vibrational and mechanical features of structure-H (sH) gas hydrate. IR spectra of different sH hydrates are obtained at 0 K at equilibrium and under applied pressure. Information about the main vibrational modes of sH hydrates and the factors that affect them such as guest type and pressure are revealed. The obtained IR spectra of sH gas hydrates agree with experimental/computational literature values. Hydrogen bond’s vibrational frequencies are used to determine the hydrate’s Young’s modulus which confirms the role of these bonds in defining sH hydrate’s elasticity. Vibrational frequencies depend on pressure and hydrate’s O···O interatomic distance. OH vibrational frequency shifts are related to the OH covalent bond length and present an indication of sH hydrate’s hydrogen bond strength. This work presents a new route to determine mechanical properties for sH hydrate based on IR spectra and contributes to the relatively small database of gas hydrates’ physical and vibrational properties.